Perbukitan Karst dan Kehidupan Manusia di Masa Lalu Arkeologi Kampung Demetin dan Sekitarnya Kemtuk - Ngaderman, Theodora; Reliubun, Lukman; Kudiai, Silvester; Rahmat, Anissa (Peneliti.net, 2024)
The research with the title karst hills and human life in the archaeological past of Demetin Village and its surroundings Kemtuk is to study the karst hills geomorphologically and what the forms and patterns of life were in the past by observing the rocks and stratigraphy in Demetin Village. Through a geomorphological approach, this approach can understand the relationship between natural landscapes and their relationship to human life. Can help determine the position of rock layers based on stratigraphy. Apart from that, you can study the ecological relationship with the environment of a site. The methods used in this research are interviews and questionnaires, measurement and observation. The geological conditions of the Demetin Village research area consist of the lithology of the oldest coral limestone, then on top of it is deposited the younger one, namely the Benai Formation calcirudite limestone (Tmpb). The geomorphology of Demetin Village is divided into two units, namely the karst hill morphology unit and the fluvial plain unit. In the karst hill morphological unit, it is found that springs and relatively shallow underground rivers with a depth of about one (1) meter have found water, this means that living people do not experience too many difficulties in meeting their needs for clean water. The Demetin Village spring is located behind the community's residential houses at a relatively close distance and what is unique is that behind every community house there is a spring